1981
DOI: 10.1161/01.hyp.3.6.682
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic mechanisms in the brain and peripheral organs of normotensive and spontaneously hypertensive rats at various ages.

Abstract: SUMMARY Previous studies of noradrenergic mechanisms in spontaneously hypertenshe rats (SHR) have yielded conflicting results, as many have used: 1) rats of only one age; 2) a single organ such as heart or brain; or 3) either Wistar-Kyoto (WKY) or an outbred normotensive control rat We have studied the turnover of norepinephrine (NE) in three brain areas (cortex, hypothalamus, brain stem) and three peripheral organs (duodenum, skeletal muscle, kidney) of SHR, WKY, and Wistar rats at 5,9, and 18 weeks of age. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…the estimates for SHRSP and WKY were in good agreement with those reported previously (16,21). These results suggested that RSNA was different among the four strains (25).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…the estimates for SHRSP and WKY were in good agreement with those reported previously (16,21). These results suggested that RSNA was different among the four strains (25).…”
Section: Discussionsupporting
confidence: 90%
“…However, due to the technical difficulties posed by the small body sizes of very young rats, we used rats of 6 to 8 weeks of age. At this age, SHRSP rapidly develop hypertension (15,16). Accordingly, a significant difference in BP was observed between the SHRSP-based and the WKY-based strains, while BP was not different between the two SHRSP-based strains nor between the two WKYbased strains.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…19 Previous research suggests that (i) brown fat emergence in WAT can be induced by sympathetic b-adrenergic stimulation [20][21][22] and (ii) dietary fat can increase sympathetic outflow from the central nervous system to the periphery. 23 Given these observations, we hypothesized that the spontaneously hypertensive rat (SHR) may be a genetic strain that is susceptible to the emergence of brown fat in WAT in response to a high-fat diet (HFD), as it is characterized by high sympathetic outflow to the periphery, including to WAT, [24][25][26][27] and shows augmentations in sympathetic activity (indicated indirectly by an augmentation in heart rate) 28 and expression of genes involved in fat burning in WAT in response to a chronic HFD. 29 SHR compared with Wistar Kyoto rats, for example, also gain less body weight in response to a chronic HFD.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that impaired neuronal L-DOPA release in the NTS of SHR is not secondarily caused by a decrease in the formation or an increase in the decarboxylation of L-DOPA, but apparently arises from the attenuation of arterial baroreceptor reflex processes involved in the release of L-DOPA. Alterations of the catecholaminergic systems in the brainstem have been reported to be involved in the development and maintenance of the hypertension (72)(73)(74)(75)(76). However, our proposed L-DOPA system in the rat NTS differs completely from catecholaminergic systems, as described in the section on normotensive Wistar rats.…”
Section: Nts-l-dopa Is Probably a Neurotransmitter Of The Primary Barmentioning
confidence: 80%